Bibliometric analyses of turnover intention among nurses: implication for research and practice in China - Zhang, Huifang; Wong, Li Ping; Hoe, V. C. W. (Frontiers in Psychology, 2023)
Objective: In order to gain insight into the latest research progress, research hotspots and development trends of turnover intention in the field of nursing, the study conducted a bibliometric analysis of the published literature to assess the research status of nurses' turnover intention. Methods: Search the WOS database from January 2017 to 2021. Articles in languages only English were excluded. The keywords used were ‘nurse*’and ‘turnover*’or ‘intention to leave". types were limited to "Article", "Review", and "Editorial". Bibliometric analysis using VOS viewer software and Citespace software Results: There is an overall upward trend in the number of articles published in the field of nursing in terms of turnover from 2017-2021. The United States has the highest number of publications and the highest number of institutions, while China ranks 2nd in terms of publications, but there are no Chinese research institutions in the top 10. The top 3 journals in terms of the number of articles published are the Journal of nursing management、Journal of advanced nursing and the Journal of clinical nursing; Oman's League had the highest number of citations for their article in 2021; most of the studies on turnover intention in nursing focused on burnout、stress、satisfaction、model、work environment、organizational commitment、perception、predictor、mental health、mediating role. Conclusions: The increasing importance of turnover intention. There is still a gap between China's influential research institution setup and the international level. Job burnout in nursing is likely to remain a research hotspot for some time, and the study's focus on moderating factors for nursing staff may be a focus for future attention.